Knowledge Transfer from Multinationals through Labour Mobility: Are There Effects on Productivity, Product Sophistication and Exporting?. Issue 12 (26th September 2019) - Masso, Jaan; Vahter, Priit
ABSTRACT: We investigate whether labour mobility from foreign-owned firms to local firms in the host economy is associated with an increase in productivity, export product complexity and other export indicators of domestic firms. Based on employer-employee level data from Estonia, we confirm that hiring employees with experience from foreign-owned firms is associated with an increase in the total factor productivity (TFP) of the firm and the higher export propensity and breadth of export markets or products. However, on average, these within-firm effects on TFP appear to be not working through increases in the level of the complexity of the export product portfolio of domestically owned firms. One implication of this result is that other channels of upgrading than changes in the Hausmann-Hidalgo export product complexity measure may be more important in this context; for example, such as upgrading the tasks or activities in the global value chain of a product.